Peran Senyawa Metabolit Sekunder Tanaman Padi terhadap Ketahanan Wereng Cokelat (Nilaparvata lugens) - Eko Hari Iswanto; R. Heru Praptana; Agus Guswara (Puslitbang Tanaman Pangan, 2016)
Resistance character to brown planthopper (BPH) is one of the main component of farmers’ interest in rice cultivation, because its utilization is convenient, inexpensive and environmental friendly, and, therefore, the technology is rapidly used by farmers in brown planthopper management. Rice resistance to BPH is related with plant secondary metabolite compounds. Oxalic acid, tricin, schaftoside, isoschaftoside and apigenin-Cglycosides have effect to BPH as deterrence, antifeeding and toxicosis. Concentration of those secondary metaboilite is higher in resistant variety than susceptible variety. Every variety has different component and composition of secondary metabolite. With specific plant secondary metabolite as marker, selection proses could be easier and faster in resistance genotype detection in a breeding program.